ANALYSIS OF THE INFLUENCE EVENTS ON THE INCREASE AND DECREASE OF WORLD OIL PRICES ON ABNORMAL RETURN AND TRADING VOLUME ACTIVITY IN MINING SECTOR COMPANIES THAT REGISTERED IN INDONESIA STOCK EXCHANGE - Stevany Stevany; Yenny Wati; Teddy Chandra; Evelyn Wijaya (International Conference on Business Management and Accounting, 2022)
This research aims to analyze the increase and decrease of oil world prices to abnormal returns and trading volume activity on mining sector companies that are registered on the Indonesia Stock Exchange. Samples used were 56 companies using the purposive sampling method. This research took abnormal return and trading volume activity to be examined. An event study was used as the research model. This study also used paired sample t-test. The results showed that the United States released oil reserves, sanctions on oil exports in Russia, Russia's import ban, the decreased supply of oil from Russia to abnormal returns both before and after the event in mining companies that registered on the Indonesia Stock Exchange. However, there is no significant difference before and after abnormal returns in all events. There is also no significant difference before and after trading volume activity at the beginning of the United States releasing oil reserves, sanctions on oil exports in Russia, Russia's import ban, and the decrease supply of oil from Russia to mining companies that registered in the Indonesia Stock Exchange. Russia's import ban event, there was significant trading volume activity in mining companies that registered on Indonesia Stock Exchange. Investors should be careful in receiving information that will affect their investment decisions.